Towards Transparency in Law (And in the Meanwhile, More Mediation) - Jaakko Henrik Salminen (Oikeustieteen ylioppilaiden yhdistys Lex ry., 2025)
In this article, I address the problem that no matter how well a law or contract is dra ed it cannot foresee and take into account all the possible contexts in which it will be utilised. Law is always relatively open-ended textual interpretation that by its nature is dependent on the perspective adopted by its interpreters, the courts, on both the legal and the factual context of a case. us, I see law as systemic discourse over societally acceptable behaviour de ned by the perspective adopted by courts on legal and contextual input. Discourse over all the possible perspectives on this input is limited by the requirement of courts to nally solve each individual dispute. Within these limits, the perspective adopted by the courts depends on the courts’ assessment of the value of the di erent kinds of input they perceive as a ecting a particular case and, through that case, the system as a whole. is starting point leads to two conclusions that are discussed in more detail.
First, legal interpretation cannot by itself be a valid source of argumentation, but rather a means of identifying valid arguments. Any choice over di erent arguments must ultimately be made in some other way. For example, Latour’s ethnographic research on the French Supreme Administrative Court indicates that the true motives behind individual judgments are extremely diverse and o en concealed om the judgments themselves. Democracy requires that increased attention should be directed to how courts in fact motivate their decisions and how these actual motivations of courts could be made more overt om a textual perspective. is will require new legal methodologies and technologies for portraying judicial actions.
Second, in order to o set the justi catory de ciencies of interpretation in legal decision- making, authors such as Pöyhönen have proposed technologies for systematizing the e ect that values might have on interpreting laws in their multiple possible contexts. However, it seems that existing law has been structurally designed to solve legal problems with little consideration of what would be the best solution in the greater context of a case, for example with regard to transaction costs, future relations, and reputation. Existing methods of creating, organizing, and systematizing law cannot take into account the wild multiplicity of these di erent contexts. is problem is especially emphasised in situations of interconnected networks of contracts. Towards this background, a more e ective way of increasing context- sensitivity is a orded by mediation. Within the amework of binding law, mediation empowers parties to explore the possibilities a orded by the context of their speci c dispute. While courts act to protect binding law, parties can override any other limits of law through the contextual eedom granted to them by mediation. us, mediation provides within the existing amework of binding law a second legal amework for increased context-sensitivity without requiring changes to existing legal paradigms.